Polyamide-based resin foamed particles

By using a mixed resin between aliphatic polyamide resin A and xylene-containing polyamide resin B, the difference in mass ratio and melting point is adjusted, and the problem of long forming cycle when the polyamide resin is foamed in the mold is solved, thereby shortening the forming cycle and improving the lightweight and design of the molded body.

CN119604567APending Publication Date: 2025-03-11JSP CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380056174.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-26
Filing Date
2023-07-24
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Due to its high softening temperature, polyamide resins require a higher forming pressure when foaming in the mold, resulting in a higher formation cost and a longer forming cycle, and the prior art has failed to effectively shorten their forming cycle.

Method used

A mixed resin of aliphatic polyamide resin A and xylene-containing polyamide resin B is used as the base resin, and the difference in mass ratio and melting point is adjusted to shorten the forming cycle of in-mold forming.

Benefits of technology

By this method, the forming cycle of the foamed polyamide resin particles can be significantly shortened, while maintaining their heat resistance, wear resistance and chemical resistance, and improving the lightweight and design properties of the molded body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604567A_ABST
    Figure CN119604567A_ABST
Patent Text Reader

Abstract

The present invention is a polyamide-based resin foamed particle in which a mixed resin of a polyamide-based resin A, which is an aliphatic polyamide, and a polyamide-based resin B, which is a xylylene group-containing polyamide resin, is used as a base resin, the mass ratio of the polyamide-based resin A to the polyamide-based resin B (polyamide-based resin A: polyamide-based resin B) is 97: 3 to 60: 40.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to polyamide resin foam particles. Background Art

[0002] Polyamide resins are known as plastics having high heat resistance and excellent wear resistance, chemical resistance, etc. Since the foamed molded article obtained by foaming the polyamide resin can achieve light weight while maintaining excellent properties such as heat resistance, wear resistance, chemical resistance, etc., it is expected to be further used in automobile parts, electrical products, etc.

[0003] For example, Patent Document 1 discloses a polyamide resin foamed molded product, which contains a polyamide resin, and when calculated based on the peak with the narrowest peak width in the X-ray diffraction spectrum, the crystallite size D is greater than a specific value, and the crystallinity X is within a specific range, and records that a polyamide resin foamed molded product with excellent heat resistance and sound insulation can be provided industrially.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2016 / 147582 Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] Since polyamide resins have a high softening temperature, they tend to require a higher molding pressure than polystyrene resins when foaming in a mold, which results in higher molding costs and longer molding cycles.

[0009] Patent Document 1 does not study the molding cycle of the polyamide-based resin foam molded article, and there is room for improvement in shortening the molding cycle of the polyamide-based resin foam molded article.

[0010] The technical problem to be solved by the present invention is to provide a polyamide resin foam particle capable of shortening the molding cycle during in-mold molding.

[0011] Solutions for solving the above technical problems

[0012] The present inventors have discovered that polyamide resin foamed particles can solve the above technical problems.

[0013] That is, the present invention is as follows.

[0014] <1> A polyamide resin foam particle, which is a polyamide resin foam particle using a mixed resin of polyamide resin A and polyamide resin B as a base resin, wherein the polyamide resin A is an aliphatic polyamide, the polyamide resin B is a polyamide resin containing xylene groups, and the mass ratio of the polyamide resin A to the polyamide resin B (polyamide resin A: polyamide resin B) is 97:3 to 60:40.

[0015] <2> The polyamide resin foamed particles according to <1>, wherein the polyamide resin B has a melt flow rate of 5 g / 10 min or less at 275° C. and a load of 0.325 kg.

[0016] <3> The polyamide resin expanded particles according to <1> or <2>, wherein the expanded particles contain carbon black.

[0017] <4> The polyamide resin expanded particles according to any one of <1> to <3>, wherein the polyamide resin A has a melting point (TmA) of more than 180°C and not more than 250°C.

[0018] <5> The polyamide resin foamed particles according to any one of <1> to <4>, wherein the difference (TmB-TmA) between the melting point (TmA) of the polyamide resin A and the melting point (TmB) of the polyamide resin B is 30°C to 100°C.

[0019] <6> The polyamide resin foamed particle according to any one of <1> to <5>, wherein the apparent density of the foamed particle is 10 kg / m 3 Above 300kg / m 3 the following.

[0020] <7> The polyamide resin expanded particles according to any one of <1> to <6>, wherein the expanded particles have a closed cell ratio of 70% or more.

[0021] <8> A polyamide resin expanded bead molded article obtained by in-mold molding the polyamide resin expanded bead according to any one of <1> to <7>.

[0022] Effects of the Invention

[0023] According to the present invention, it is possible to provide polyamide resin foamed particles capable of shortening the molding cycle during in-mold molding. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a diagram illustrating the first DSC curve of polyamide resin foamed particles. DETAILED DESCRIPTION

[0025] [Foaming particles]

[0026] The polyamide resin foamed particles of the present invention (hereinafter also referred to as "polyamide resin foamed particles" or "foamed particles") are polyamide resin foamed particles using a mixed resin of polyamide resin A and polyamide resin B as a base resin, wherein the polyamide resin A is an aliphatic polyamide, the polyamide resin B is a polyamide resin containing xylene groups, and the mass ratio of the polyamide resin A to the polyamide resin B (polyamide resin A: polyamide resin B) is 97:3 to 60:40.

[0027] <Base resin>

[0028] (Polyamide resin A)

[0029] The polyamide resin A constituting the mixed resin of the base resin of the polyamide resin foamed particles of the present invention is an aliphatic polyamide. Examples of the aliphatic polyamide include aliphatic homopolyamide, aliphatic polyamide copolymers, and mixtures thereof. A polyamide copolymer refers to a copolymer having two or more repeating units and having an amide bond in at least a portion of each repeating unit.

[0030] Examples of the aliphatic homopolyamide include poly(6-aminocaproic acid) (polycaproamide, nylon 6) also known as poly(caprolactam), poly(laurolactam) (nylon 12), poly(hexamethylenediamine adipamide) (nylon 66), poly(7-aminoheptanoic acid) (nylon 7), poly(8-aminooctanoic acid) (nylon 8), poly(9-aminononanoic acid) (nylon 9), poly(10-aminodecanoic acid) (nylon 10), poly(11-aminoundecanoic acid) (nylon 11), poly(hexamethylenediamine sebacate) (nylon 610), poly(decamethylenediamine sebacate) (nylon 1010), poly(hexamethylenediamine azelaic acid) (nylon 69), poly(butylene adipamide) (nylon 46), poly(butylene adipamide) (nylon 410), poly(pentamethylenediamine adipamide) (nylon 56), and poly(pentamethylenediamine sebacate) (nylon 510).

[0031] Examples of the aliphatic polyamide copolymer include polycaproamide / polyhexamethylene adipamide copolymer (nylon 6 / 66), caprolactam / hexamethylenediaminoadipic acid / laurolactam (nylon 6 / 66 / 12), and caprolactam / laurolactam copolymer (nylon 6 / 12).

[0032] The polyamide-based resin A may be used alone or in combination of two or more. It may also be a mixture of an aliphatic homopolyamide and an aliphatic polyamide copolymer.

[0033] Among them, the polyamide resin A is preferably one or more selected from the group consisting of nylon 6, nylon 66, nylon 6 / 66, and nylon 6 / 66 / 12, and more preferably one or more selected from the group consisting of nylon 6 / 66 and nylon 6 / 66 / 12.

[0034] The polyamide copolymer may be a block copolymer in which a certain amount of amide of the same repeating unit continues and then a certain amount of different types of amide continues, or may be a random copolymer in which different types of amide are randomly repeated, preferably a random copolymer. If the polyamide copolymer is a random copolymer, it can be formed at a relatively low forming pressure when the foamed particles are molded.

[0035] The polyamide resin A is preferably a blocked polyamide resin having blocked functional groups at the ends of the molecular chains. Thus, hydrolysis during the manufacturing process of the expanded particles can be more reliably suppressed, and expanded particles that can withstand in-mold molding can be easily obtained, and the durability of the polyamide resin expanded particle molded body (hereinafter, also referred to as "expanded particle molded body" or "molded body") is improved.

[0036] As the end-capping agent for capping the ends of the molecular chains, for example, a carbodiimide compound, an oxazoline compound, an isocyanate compound, an epoxy compound, etc. can be used.

[0037] Among them, the end-capping agent is preferably a carbodiimide compound. As the carbodiimide compound, for example, aromatic monocarbodiimides such as bis(dipropylphenyl)carbodiimide (for example, "Stabaxol 1-LF" manufactured by Rhein Chemie, etc.), aromatic polycarbodiimides (for example, "Stabaxol P", "Stabaxol P100", "Stabaxol P400" manufactured by Rhein Chemie, etc.), aliphatic polycarbodiimides such as poly(4,4'-dicyclohexylmethanecarbodiimide) (for example, "Carbodilite LA-1" manufactured by Nisshinbo Chemical Co., Ltd., etc.), etc. can be cited. These end-capping agents can be used alone or in combination of two or more.

[0038] The amount of the end-capping agent blended in the base resin is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and is preferably 5% by mass or less, more preferably 3% by mass or less. That is, the amount of the end-capping agent blended in the base resin is preferably 0.1 to 5% by mass, more preferably 0.5 to 3% by mass.

[0039] Thus, the polyamide resin A is preferably a polyamide resin end-capped with one or more end-capping agents selected from the group consisting of carbodiimide compounds, epoxy compounds and isocyanate compounds, more preferably a polyamide resin end-capped with a carbodiimide compound, and even more preferably a polyamide resin end-capped with an aromatic polycarbodiimide.

[0040] (Polyamide resin B)

[0041] The polyamide resin B is a polyamide resin containing xylylene groups. The polyamide resin containing xylylene groups is a polymer formed by polycondensing a diamine containing xylylenediamine with a dicarboxylic acid, and has a structural unit derived from xylylenediamine and a structural unit derived from dicarboxylic acid. The structural unit derived from diamine (diamine unit) of the polyamide resin containing xylylene groups preferably contains 50 mol% or more of the structural unit derived from xylylenediamine, more preferably 70 mol% or more, further preferably 80 mol% or more, further preferably 90 mol% or more, and may contain 100 mol%.

[0042] As the xylylenediamine, it is preferred that at least one of m-xylylenediamine and p-xylylenediamine is contained, and it is more preferred that m-xylylenediamine is contained.

[0043] The diamine units constituting the xylylene group-containing polyamide resin preferably contain 50 mol% or more of structural units derived from meta-xylylenediamine, more preferably 70 mol% or more, further preferably 80 mol% or more, further preferably 90 mol% or more, and may contain 100 mol%.

[0044] The diamine units in the xylylene group-containing polyamide resin may be composed of structural units derived from xylylenediamine alone, or may contain structural units derived from diamines other than xylylenediamine. Examples of diamines other than xylylenediamine include aliphatic diamines having a linear or branched structure, such as ethylenediamine, tetramethylenediamine, pentamethylenediamine, 2-methylpentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethyl-hexamethylenediamine, and 2,4,4-trimethyl-hexamethylenediamine; 1,3-bis(amino)-1,3-diamine; and Alicyclic diamines such as bis(4-aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decahydronaphthalene, and bis(aminomethyl)tricyclodecane; diamines having an aromatic ring such as bis(4-aminophenyl)ether, p-phenylenediamine, m-phenylenediamine, and bis(aminomethyl)naphthalene.

[0045] In the polyamide resin containing xylene groups, compounds that can constitute dicarboxylic acid units include α,ω-straight-chain aliphatic dicarboxylic acids with a carbon number of 4 to 20, such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; other aliphatic dicarboxylic acids such as dimer acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, xylene dicarboxylic acid, and naphthalene dicarboxylic acid; and the like.

[0046] Among them, as the compound that can constitute the dicarboxylic acid unit, preferably an α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 20 carbon atoms, more preferably at least one selected from the group consisting of adipic acid and sebacic acid, and still more preferably adipic acid.

[0047] The dicarboxylic acid-derived structural units (dicarboxylic acid units) of the xylylene group-containing polyamide resin preferably contain 50 mol% or more of structural units derived from adipic acid, more preferably 70 mol% or more, further preferably 80 mol% or more, further preferably 90 mol% or more, and may contain 100 mol%.

[0048] That is, the polyamide resin B preferably has a structural unit derived from a diamine, wherein the diamine contains 50 mol% or more of a structural unit derived from meta-xylylenediamine, and the dicarboxylic acid contains 50 mol% or more of a structural unit derived from adipic acid, and more preferably has a structural unit derived from a diamine, wherein the diamine contains 80 mol% or more of a structural unit derived from meta-xylylenediamine, and the dicarboxylic acid contains 80 mol% or more of a structural unit derived from adipic acid, and further preferably has a structural unit derived from a diamine, wherein the diamine contains 90 mol% or more of a structural unit derived from meta-xylylenediamine, and the dicarboxylic acid contains 90 mol% or more of a structural unit derived from adipic acid, and may have a structural unit derived from a diamine, wherein the diamine contains 100 mol% of a structural unit derived from meta-xylylenediamine, and the dicarboxylic acid contains 100 mol% of a structural unit derived from adipic acid.

[0049] As the diamine units constituting the remainder other than meta-xylylenediamine, structural units derived from p-xylylenediamine are preferred.

[0050] As the dicarboxylic acid unit of the remainder excluding adipic acid, a structural unit derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms is preferred.

[0051] In addition to the above-mentioned diamines and dicarboxylic acids, as components constituting the xylene-containing polyamide resin, lactams such as ε-caprolactam and laurolactam, aliphatic aminocarboxylic acids such as aminocaproic acid and aminoundecanoic acid; and aromatic aminocarboxylic acids such as p-aminomethylbenzoic acid can also be used as copolymer components within the range not impairing the effects of the present invention.

[0052] 《Melt Flow Rate (MFR)》

[0053] From the viewpoint of shortening the molding cycle, the melt flow rate (MFR) of the polyamide resin B at 275°C and a load of 0.325kg is preferably 10 g / 10 minutes or less, more preferably 8 g / 10 minutes or less, and further preferably 5 g / 10 minutes or less, and its lower limit is not particularly limited, and is 0.1 g / 10 minutes or more. The melt flow rate of the polyamide resin B is a value measured based on JIS K7210-2:2014 at a test temperature of 275°C and a rated load of 0.325kg. In addition, a sample having a water content of 1000 mass ppm or less is used as a measurement sample.

[0054] (Mass ratio of polyamide resin A to polyamide resin B)

[0055] The mass ratio of polyamide resin A to polyamide resin B in the base resin (polyamide resin A: polyamide resin B) is 97:3 to 60:40. From the viewpoint of shortening the molding cycle during in-mold molding, the mass ratio of polyamide resin B is preferably 5% by mass or more, more preferably 7% by mass or more, and further preferably 10% by mass or more (wherein the total of the content of polyamide resin A and the content of polyamide resin B in the base resin is 100% by mass). On the other hand, from the viewpoint of further suppressing the shrinkage of the molded body, the mass ratio of polyamide resin A is preferably 70% by mass or more, more preferably 75% by mass or more, and further preferably 80% by mass or more (wherein the total of the content of polyamide resin A and the content of polyamide resin B in the base resin is 100% by mass). That is, the above mass ratio (polyamide resin A: polyamide resin B) is preferably 95:5 to 70:30, more preferably 93:7 to 75:25, and further preferably 90:10 to 80:20.

[0056] (Melting Point of Polyamide Resin A (TmA) and Melting Point of Polyamide Resin B (TmB))

[0057] The melting point (TmA) of the polyamide resin A and the melting point (TmB) of the polyamide resin B can be determined from the second DSC curve obtained under the following condition 1.

[0058] Condition 1

[0059] Heat flux differential scanning calorimetry according to JIS K7121-1987, with expanded beads as test pieces, the DSC curve measured when heated from 30°C at a heating rate of 10°C / min to a temperature 30°C higher than the end of the melting peak for melting is the first DSC curve, and the DSC curve measured when the temperature is maintained for 10 minutes, cooled to 30°C at a cooling rate of 10°C / min, and heated again at a heating rate of 10°C / min to a temperature 30°C higher than the end of the melting peak for melting is the second DSC curve. In addition, a sample with a water content of 1000 mass ppm or less is used as a measurement sample.

[0060] In the second DSC curve, there are a melting peak (I) inherent to the polyamide resin A and a melting peak (III) inherent to the polyamide resin B at a higher temperature side than the melting peak (I). The temperature of the top of the melting peak (I) of the second DSC curve is equivalent to the melting point (TmA) of the polyamide resin A as a raw material for manufacturing foamed particles, and the temperature of the top of the melting peak (III) of the second DSC curve is equivalent to the melting point (TmB) of the polyamide resin B as a raw material for manufacturing foamed particles. The melting peak (I) and the melting peak (III) appear in the first DSC curve and also in the second DSC curve. Sometimes the temperatures of the tops of the melting peak (I) and the melting peak (III) are slightly different in the first DSC curve and the second DSC curve, respectively, but usually the difference is about 5°C or less.

[0061] (Difference (TmB-TmA))

[0062] From the viewpoint of secondary foaming and weldability of the expanded particles during in-mold molding, the difference (TmB-TmA) between the melting point (TmA) of the polyamide resin A and the melting point (TmB) of the polyamide resin B in the base resin is preferably 20°C or more, more preferably 30°C or more, further preferably 35°C or more, and further preferably 40°C or more, and preferably 100°C or less, more preferably 80°C or less, further preferably 60°C or less, and further preferably 55°C or less. That is, the difference (TmB-TmA) is preferably 20 to 100°C, more preferably 30 to 100°C, further preferably 30 to 80°C, further preferably 35 to 60°C, and particularly preferably 40 to 55°C. The difference (TmB-TmA) between the melting point (TmA) of polyamide resin A and the melting point (TmB) of polyamide resin B can be obtained from the difference between the melting point (TmA) of polyamide resin A and the melting point (TmB) of polyamide resin B in the second DSC curve using the foamed particles as the test piece.

[0063] 《Melting Point (TmA)》

[0064] From the viewpoint of improving the heat resistance of the polyamide resin expanded bead molded article formed by mutually fusing the polyamide resin expanded bead molded article of the present invention, the melting point (TmA) of the polyamide resin A is preferably 150°C or higher, more preferably 160°C or higher, further preferably 170°C or higher, and further preferably more than 180°C, and from the viewpoint of improving the fusing property of the expanded bead and improving the lightness of the molded article, it is preferably 250°C or lower, more preferably 230°C or lower, further preferably 210°C or lower, further preferably 200°C or lower, and further preferably 190°C or lower. That is, TmA is preferably 150 to 250°C, more preferably 160 to 230°C, further preferably 170 to 210°C, further preferably more than 180°C and 190°C or lower.

[0065] Melting Point (TmB)

[0066] From the viewpoint of improving the heat resistance of the molded article, the melting point (TmB) of the polyamide resin B is preferably 200°C or higher, more preferably 210°C or higher, further preferably 220°C or higher, and further preferably 230°C or higher, and from the viewpoint of improving the weldability of the foamed particles, it is preferably 270°C or lower, more preferably 260°C or lower, further preferably 250°C or lower, and further preferably 240°C or lower. That is, TmB is preferably 200 to 270°C, more preferably 210 to 260°C, further preferably 220 to 250°C, and further preferably 230 to 240°C.

[0067] In the condition 1, in the first DSC curve using expanded particles as a test piece, there is sometimes a melting peak (II), which is closer to the high temperature side than the melting peak (I) inherent in polyamide resin A, and is caused by the secondary crystallization of the polyamide resin formed by the thermal process until the resin particles are foamed to obtain the expanded particles. In this specification, the melting peak (II) is referred to as the high temperature peak. There are sometimes more than 2 high temperature peaks (melting peaks (II)). In addition, no high temperature peak (melting peak (II)) is confirmed in the second DSC curve. In the first DSC curve using expanded particles as a test piece, the temperature of the top of the high temperature peak (melting peak (II)) appears on the high temperature side more than the melting peak (I). In addition, although it also depends on the temperature difference between the top temperature of the melting peak inherent in polyamide resin A and the top temperature of the melting peak inherent in polyamide resin B, it is preferred that the temperature of the top of the high temperature peak (melting peak (II)) is present between the melting peak (I) and the melting peak (III) in the first DSC curve. That is, in the 1st DSC curve obtained by the condition 1, it is preferred that there is a melting peak (I), a melting peak (II), and a melting peak (III) in sequence from the low temperature side. High temperature peak occurs on the high temperature side more close to the melting peak (I) intrinsic to polyamide resin A. Therefore, it can be considered that, compared with the melting peak (I) intrinsic to polyamide resin A, the crystallization of high temperature peak is more difficult to melt during in-mold forming, and crystallization is more likely to remain. It can be considered that, in addition to containing the polyamide resin B, when polyamide resin A has a high temperature peak, it is easier to suppress the excessive occurrence of secondary foaming, and the excessive rise of the maximum surface pressure of expanded particles relative to the forming mold is also suppressed. As a result, it can be considered that when polyamide resin A has a high temperature peak, the surface pressure reduction during water cooling becomes faster, and then the water cooling time is shortened.

[0068] The difference between the temperature of the top of the melting peak (I) and the temperature of the top of the high temperature peak is preferably 10°C or more, more preferably 12°C or more, and further preferably 15°C or more. On the other hand, the difference between the temperature of the top of the melting peak (I) and the temperature of the top of the high temperature peak is preferably 40°C or less, more preferably 30°C or less, and further preferably 25°C or less. That is, the difference between the temperature of the top of the melting peak (I) and the temperature of the top of the high temperature peak is preferably 10 to 40°C, more preferably 12 to 30°C, and further preferably 15 to 25°C. In addition, in the comparison of the temperature difference between the melting peak (I) and the top of the high temperature peak, when two or more high temperature peaks appear in the first DSC curve, the temperature of the top of the high temperature peak on the lowest temperature side is compared with the temperature of the top of the melting peak (I).

[0069] In the first DSC curve, the melting heat of the inherent melting peak (I) of the polyamide resin A is preferably 25 J / g or more, and more preferably 30 J / g or more. The melting heat of the inherent melting peak (I) of the polyamide resin A is preferably 60 J / g or less, and more preferably 50 J / g or less. That is, in the first DSC curve, the melting heat of the inherent melting peak (I) of the polyamide resin A is preferably 25 to 60 J / g, and more preferably 30 to 50 J / g. In the first DSC curve, the melting heat of the inherent melting peak (III) of the polyamide resin B is preferably 3 J / g or more, and more preferably 4 J / g or more. The melting heat of the inherent melting peak (III) of the polyamide resin B is preferably 15 J / g or less, and more preferably 10 J / g or less. That is, in the first DSC curve, the melting heat of the inherent melting peak (III) of the polyamide resin B is preferably 3 to 15 J / g, and more preferably 4 to 10 J / g. In the first DSC curve, the heat of fusion of the high temperature peak (melting peak (II)) is preferably 1 J / g or more, more preferably 2 J / g or more. The heat of fusion of the high temperature peak (melting peak (II)) is preferably 13 J / g or less, more preferably 10 J / g or less. That is, in the first DSC curve, the heat of fusion of the high temperature peak (melting peak (II)) is preferably 1 to 13 J / g, more preferably 2 to 10 J / g. Here, the temperature and heat of fusion of the apex of each melting peak can be calculated as follows.

[0070] The temperature of the top of each melting peak can be obtained from the melting peak obtained in the first DSC curve obtained when the temperature is increased from 30°C to 30°C higher than the temperature at the end of the melting peak at a heating rate of 10°C / min by heat flux differential scanning calorimetry as the condition 1. The melting heat of each melting peak can be obtained based on the DSC curve obtained by the following condition 2. In addition, a high-sensitivity differential scanning calorimeter "EXSTAR DSC7020" (manufactured by Seiko NanoTech (SII NanoTech) Co., Ltd.) can be used as a measuring device.

[0071] Condition 2

[0072] According to the heat flux differential scanning calorimetry method of JIS K7122-1987, expanded beads are used as test pieces and heated at a heating rate of 10°C / min from 30°C to a temperature 30°C higher than the end of the melting peak to melt and obtain the first DSC curve.

[0073] Below, with Figure 1 (1st DSC curve) is used as an example to explain in detail. Figure 1In the first DSC curve shown, there are three melting peaks, the lowest temperature side peak is the melting peak (I) inherent to the polyamide resin A, the second peak is a high temperature peak (melting peak (II)), and the highest temperature side peak is the melting peak (III) inherent to the polyamide resin B. The temperature of the top of each melting peak is the temperature of the point where the heat absorption of each peak is the largest.

[0074] exist Figure 1 In the DSC curve shown, the melting heat of the apex of each melting peak is equivalent to the area of ​​each melting peak, which can be obtained as follows. Draw a straight line (derived from the baseline of the melting peak of polyamide resin A) connecting the point of 120°C on the DSC curve and the point on the DSC curve showing the melting end temperature of the melting peak (II). The melting peak (I) and the melting peak (II) are divided by a straight line perpendicular to the temperature of the horizontal axis of the graph from the point on the DSC curve corresponding to the valley between the melting peak (I) and the melting peak (II) to the baseline of the melting peak derived from the polyamide resin A. The area 1 of the peak on the low temperature side divided is equivalent to the melting heat of the melting peak (I) inherent in the polyamide resin A, and the area 2 of the peak on the high temperature side divided is equivalent to the melting heat of the high temperature peak (melting peak (II)) caused by the secondary crystallization of the polyamide resin formed by the thermal process until the resin particles are foamed to obtain the foamed particles.

[0075] A straight line (baseline of the melting peak inherent to polyamide resin B) is drawn connecting the point on the DSC curve showing the melting start temperature of the melting peak (III) and the point showing the melting end temperature of the melting peak (III) inherent to polyamide resin B. The area 3 of the portion surrounded by the baseline of the melting peak derived from the polyamide resin B and the DSC curve is equivalent to the heat of fusion of the melting peak (III) inherent to polyamide resin B.

[0076] The base resin may contain other thermoplastic resins in addition to the polyamide resin A and the polyamide resin B, within the scope not hindering the purpose and effect of the present invention. Examples of other thermoplastic resins include polyethylene resins, polypropylene resins, polystyrene resins, vinyl acetate resins, thermoplastic polyester resins, acrylate resins, methacrylate resins, modified polyphenylene ether resins, polycarbonate resins, polyacetal resins, polybutylene terephthalate resins, polysulfone resins, polyethersulfone resins, polyamide-imide resins, polyetherimide resins, polyetheretherketone resins, and polyamide resins other than the polyamide resin A and the polyamide resin B.

[0077] From the viewpoint of obtaining foamed particles having excellent heat resistance, wear resistance and chemical resistance, the content of other thermoplastic resins in the base resin is preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 3% by mass or less. It is particularly preferred that the base resin consists only of polyamide resin A and polyamide resin B.

[0078] (Heat Stabilizer)

[0079] The foamed beads of the present invention may be blended with a heat stabilizer depending on the purpose of the molded article. The heat stabilizer has the effect of suppressing the degradation of the resin caused by heat when the foamed beads or the foamed bead molded article are placed in a high temperature environment. It is preferred to blend the heat stabilizer in the foamed beads.

[0080] When a heat stabilizer is blended in the expanded particles, the heat stabilizer may, for example, be a hindered amine compound, a hindered phenol compound, a phosphorus compound, a copper compound, or a halide.

[0081] Specific examples of hindered amine compounds include bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (trade name: Tinuvin 770, manufactured by BASF Japan). Specific examples of hindered phenol compounds include N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)) (trade name: Irganox 1098, manufactured by BASF Japan). Specific examples of phosphorus compounds include tris(2,4-di-tert-butylphenyl)phosphite (trade name: Irgafos 168, manufactured by BASF Japan). Copper compounds do not include halides described below, and examples thereof include natural minerals such as hydrotalcite, magnesite, and magnesia in addition to copper chloride, copper bromide, copper iodide, copper phosphate, and copper stearate. Examples of the halide include ammonium iodide, stearyltriethylammonium bromide, benzyltriethylammonium iodide; alkali metal halides such as potassium chloride, sodium chloride, potassium bromide, potassium iodide and sodium iodide.

[0082] Among them, from the viewpoint of imparting better weather resistance to the molded article, the heat stabilizer is preferably one or more selected from the group consisting of hindered amine compounds, hindered phenol compounds, phosphorus compounds, copper compounds and halides, more preferably one or more selected from the group consisting of copper compounds and halides, further preferably one or more selected from the group consisting of copper compounds and halogenated alkali metal salts, further preferably one or more selected from the group consisting of copper iodide and potassium iodide, and further preferably contains copper iodide and potassium iodide.

[0083] The amount of the heat stabilizer in the expanded particles is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and preferably 5% by mass or less, more preferably 3 parts by mass or less. That is, the amount of the heat stabilizer in the expanded particles is preferably 0.1 to 5% by mass, more preferably 0.2 to 3% by mass. In addition, when two or more heat stabilizers are included, the total amount is preferably within the above range.

[0084] (Colorant)

[0085] The expanded particles of the present invention preferably contain a colorant. As the colorant, an inorganic or organic pigment or dye can be used. The colorant is used to improve the appearance of the obtained molded body and enhance the design.

[0086] Examples of the inorganic pigment include titanium oxide, carbon black, titanium yellow, iron oxide, ultramarine, cobalt blue, calcined pigments, metallic pigments, mica, pearlescent pigments, zinc white, precipitated silica and cadmium red.

[0087] Examples of the organic pigment include monoazo pigments, condensed azo pigments, anthraquinone pigments, isoindolinone pigments, perinone pigments, quinacridone pigments, perylene pigments, thioindigo pigments, dioxazine pigments, phthalocyanine pigments, nitroso pigments and organic fluorescent pigments.

[0088] Examples of the dye include anthraquinone dyes, perinone dyes, basic dyes, acid dyes, and mordant dyes.

[0089] Among them, the colorant is preferably an organic pigment or an inorganic pigment from the viewpoint of weather resistance, more preferably an inorganic pigment from the viewpoint of heat resistance and weather resistance, and further preferably carbon black from the viewpoint of facilitating shortening of the molding cycle.

[0090] When the expanded particles contain a colorant, the amount of the colorant blended in the expanded particles is preferably 0.5% by mass or more, more preferably 0.8% by mass or more, and even more preferably 1% by mass or more, and is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, from the viewpoint of imparting excellent design properties to the obtained expanded particle molded article. That is, the amount of the colorant blended in the expanded particles is preferably 0.5 to 10% by mass, more preferably 0.8 to 5% by mass, and even more preferably 1 to 3% by mass.

[0091] The foamed particles may be appropriately blended with various additives such as commonly used antistatic agents, conductivity imparting agents, lubricants, ultraviolet absorbers, flame retardants, metal deactivators, crystal nucleating agents, and fillers as needed. The amount of these various additives added varies depending on the purpose of use of the molded article, but is preferably 25 parts by mass or less, more preferably 15 parts by mass or less, further preferably 10 parts by mass or less, and further preferably 5 parts by mass or less relative to 100 parts by mass of the foamed particles.

[0092] <Apparent density>

[0093] From the viewpoint of suppressing the shrinkage of the molded article and, as a result, obtaining a more excellent molded article, the apparent density of the expanded particles is preferably 10 kg / m 3 More than 30 kg / m 3 More preferably, 50 kg / m 3 More preferably, 70 kg / m 3 More than, and preferably 300kg / m 3 Below, more preferably 250kg / m 3 Below, more preferably 200kg / m 3 That is, the apparent density of the expanded particles is preferably 10 to 300 kg / m 3 , more preferably 30 to 300 kg / m 3 , more preferably 50 to 250 kg / m 3 , more preferably 70 to 200 kg / m 3 .

[0094] The apparent density of the expanded particles was measured by the following method. A graduated cylinder filled with water at a temperature of 23° C. was prepared, and the volume of about 500 cm 2 of the expanded particles was measured after being left for 2 days under the conditions of a relative humidity of 50%, 23° C., and 1 atm. 3 The mass W1 of the foamed particles is then sunk into the measuring cylinder using a wire mesh. Taking into account the volume of the wire mesh, the volume V1 [cm 3 ], the mass W1[g] of the foamed particles is divided by the volume V1 to calculate (W1 / V1), and the unit is converted to [kg / m 3 ], calculate the apparent density of the foamed particles.

[0095] <Average bubble diameter>

[0096] From the viewpoint of easily obtaining a molded body with excellent surface properties, the average cell diameter of the expanded particles is preferably 30 μm or more, more preferably 50 μm or more, further preferably 70 μm or more, further preferably 90 μm or more, and is preferably 250 μm or less, more preferably 200 μm or less, further preferably 170 μm or less, further preferably 150 μm or less. That is, the average cell diameter of the expanded particles is preferably 30 to 250 μm, more preferably 50 to 200 μm, further preferably 70 to 170 μm, further preferably 90 to 150 μm.

[0097] The average bubble diameter of the foamed particles is measured by the following method. First, the foamed particles are roughly divided into two equal parts in a manner passing through the center of the foamed particles, and a photo of the cut surface is taken using a scanning electron microscope. Then, in the obtained cross-sectional photo, straight lines are drawn at equal intervals in 8 directions from near the center of the cut surface of the foamed particles, and the number of bubbles intersecting the straight lines is counted. The total length of the straight line is divided by the number of bubbles counted, and the obtained value is used as the bubble diameter of the foamed particles. The same operation is performed on more than 10 foamed particles, and the arithmetic mean of the bubble diameters of each foamed particle is used as the average bubble diameter of the foamed particles.

[0098] <Closed cell diameter>

[0099] From the viewpoint of easily obtaining a molded body having excellent weldability and restorability, the closed cell ratio of the expanded beads is preferably 70% or more, more preferably 80% or more, further preferably 85% or more, and further preferably 90% or more.

[0100] The closed cell ratio of expanded beads is the ratio of the volume of closed cells to the volume of all cells in the expanded beads, and can be determined using an air comparative densitometer based on ASTM-D2856-70.

[0101] [Method for producing expanded particles]

[0102] In the method for producing polyamide resin foamed particles of the present invention, resin particles using a mixed resin of the polyamide resin A and the polyamide resin B as a base resin are foamed to produce polyamide resin foamed particles.

[0103] <Resin particles using mixed resin as base resin and method for producing the same>

[0104] The mass of one of the resin particles is appropriately set according to the size of the target foamed particles, the apparent density, etc., but is preferably 0.5 mg or more and 15.0 mg or less. If it is within the above range, the apparent density can be increased. From the above viewpoints, the mass of the resin particles is more preferably 1.0 mg or more, more preferably 1.5 mg or more, and more preferably 10.0 mg or less, more preferably 7.0 mg or less, and even more preferably 5.0 mg or less. That is, the mass of the resin particles is more preferably 1.0 to 10.0 mg, more preferably 1.5 to 7.0 mg, and even more preferably 1.5 to 5.0 mg.

[0105] From the viewpoint of obtaining foamed particles with excellent heat resistance, the melting point (Tm) of the resin particles is preferably 180°C or more, more preferably 183°C or more, and further preferably 185°C or more, and from the viewpoint of easy temperature control during foaming, it is preferably 250°C or less, more preferably 220°C or less, and further preferably 200°C or less. That is, Tm is preferably 180-250°C, more preferably 183-220°C, and further preferably 185-200°C. In addition, the melting point of the resin particles refers to the melting point of a kneaded product obtained by kneading the polyamide resin A and the polyamide resin B in advance by an extruder or the like. In the case where the DSC curve has multiple melting peaks, the peak top temperature of the melting peak with the largest area is adopted as the melting point.

[0106] By using a common extruder, polyamide resin A and polyamide resin B are melt-kneaded, and a mixed resin of melt-kneaded polyamide resin A and polyamide resin B can be obtained. The extruder can use any one of a single screw and a twin screw. The manufacturing method of resin particles is not particularly limited and can be obtained by a known method. For example, polyamide resin A, polyamide resin B, additives such as colorants and bubble regulators as required are put into an extruder, kneaded and made into a melt-kneaded product, and the melt-kneaded product is extruded into a wire bundle from a small hole of a die head attached to the front end of the extruder, and the extruded melt is cooled and solidified, and then cut into a specified mass with a granulator, and resin particles can be obtained by the wire bundle cutting method, the heat cutting method of cutting off the melt-kneaded product immediately after being extruded into the gas phase, and the underwater cutting method (UWC method) of cutting off the melt-kneaded product immediately after being extruded into water, etc.

[0107] (Example of a method for producing expanded particles)

[0108] The foamed particles of the present invention can be produced, for example, by a manufacturing method having a "foaming step", wherein the "foaming step" causes the resin particles having the mixed resin as the base resin to be impregnated with a foaming agent, and the resin particles having the mixed resin as the base resin impregnated with the foaming agent are foamed by heating, pressure change, volume change, etc.

[0109] 《Foaming agent adding process》

[0110] The foaming agent adding step is a step of adding a foaming agent into a closed container. It is preferred that the foaming agent is impregnated into the resin particles in this step, and foamable resin particles can also be made. The foaming agent can be impregnated into the resin particles in this step and each step described later (dispersion step, heating step, holding step), and foamable resin particles can be obtained. In addition, in this step, when the foaming agent is impregnated, it is preferred that the resin particles are dispersed in an aqueous solvent in a pressurized closed container such as an autoclave, and the foaming agent is impregnated into the resin particles. As the aqueous solvent, water is preferred. In addition, from the viewpoint of fully impregnating the resin particles with the foaming agent in a short time, the impregnation of the resin particles with the foaming agent is preferably carried out by pressurization and / or heating.

[0111] (foaming agent)

[0112] In the method for producing the expanded particles of the present invention, a physical foaming agent is preferably used as a foaming agent. As the physical foaming agent, an organic physical foaming agent may include aliphatic hydrocarbons such as propane, butane, pentane, hexane, and heptane; alicyclic hydrocarbons such as cyclopentane and cyclohexane; halogenated hydrocarbons such as hydrofluoroolefins, chlorofluoromethane, trifluoromethane, 1,1-difluoroethane, 1,1,1,2-tetrafluoroethane, methyl chloride, ethyl chloride, and dichloromethane; dialkyl ethers such as dimethyl ether, diethyl ether, and methyl ethyl ether. In addition, as an inorganic physical foaming agent, carbon dioxide, nitrogen, helium, argon, air, etc. may be mentioned.

[0113] Among physical blowing agents, inorganic physical blowing agents are preferred, carbon dioxide or nitrogen is more preferred, and carbon dioxide is further preferred, from the viewpoint of having little impact on the environment, being non-flammable and having excellent safety.

[0114] In addition, in order to fully impregnate the resin particles with the foaming agent in a short time, this process is preferably carried out under pressure. Regarding the maximum pressure during impregnation under pressure (hereinafter also referred to as impregnation pressure), from the viewpoint of fully impregnating the resin particles with the foaming agent in a short time, by adding the foaming agent to the container containing the dispersion liquid, it is preferred that the pressure in the closed container be 1.5MPa(G) or more, more preferably 2.5MPa(G) or more, and preferably 7MPa(G) or less, more preferably 5MPa(G) or less. That is, the pressure in the closed container to which the foaming agent is added is preferably 1.5 to 7MPa(G), more preferably 2.5 to 5MPa(G). In addition, "1.5MPa(G)" means that the instrument pressure is 1.5MPa.

[0115] (Example of Manufacturing Method)

[0116] The method for producing the foamed particles of the present invention is not limited as long as it comprises the above-mentioned "foaming agent adding step" and "foaming step", but preferably comprises [1] a method in which the resin particles impregnated with the foaming agent are impregnated with the foaming agent, the resin particles impregnated with the foaming agent are taken out without foaming, and then heated in a foaming device to obtain foamed particles; and [2] a method in which the resin particles dispersed in a dispersion medium in a closed device are impregnated with the foaming agent, the temperature is raised to near the softening temperature of the resin, and then the resin particles are discharged to the outside of the device under low pressure together with the dispersion medium to obtain foamed particles. The method [2] is more preferred.

[0117] A preferred production method as the method [2] is described below.

[0118] The method for producing the expanded beads of the present invention preferably includes the following steps.

[0119] (1) a dispersing step of dispersing the resin particles using the mixed resin as the base resin in water in a sealed container to obtain a dispersion;

[0120] (2) a heating step of heating the dispersion liquid;

[0121] (3) A holding step of holding the dispersion at a temperature 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher and lower than a temperature 50°C lower than Tm (Tm-50°C) for a holding time of 1 minute to 60 minutes.

[0122] (4) A foaming step, wherein the temperature (Te) of the dispersion immediately before foaming is set to a temperature that is 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher and lower than a temperature that is 50°C lower than Tm (Tm-50°C), and the resin particles containing a foaming agent are released from a closed container together with water at a pressure lower than the pressure in the closed container to foam them.

[0123] The method for producing the expanded beads of the present invention may include steps other than the above steps, and other components may be further added to the above steps.

[0124] 《Dispersion process》

[0125] The dispersing step is a step of dispersing the resin particles in an aqueous solvent, preferably water, in a closed container to obtain a dispersion.

[0126] The method for dispersing the resin particles in water is not particularly limited, and a known method can be used. For example, a dispersion can be obtained by adding the resin particles to water while stirring the water using a stirrer and further stirring the water.

[0127] In addition, it is preferred to add dispersants such as inorganic substances such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, zinc oxide, kaolin, mica, talc, montmorillonite, and dispersants such as anionic surfactants such as sodium dodecylbenzene sulfonate and sodium alkyl sulfonate to the dispersion liquid as needed. The mass ratio of resin particles to dispersants (resin particles / dispersants) is preferably set to 20 to 2000, more preferably 30 to 1000. In addition, the mass ratio of dispersants to dispersants (dispersants / dispersants) is preferably set to 1 to 500, more preferably 1 to 100.

[0128] 《Heating process》

[0129] The heating process is an arbitrary process in the manufacture of expanded particles. The heating process can be arranged before the foaming agent adding process, can also be arranged after the foaming agent adding process, and can also be arranged in the foaming agent adding process. In this process, it is preferred to heat the dispersion liquid to the foaming temperature or the holding temperature described later. It can be considered that in the above-mentioned heating process, the water in the aqueous solvent is more easily absorbed by the polyamide resin.

[0130] The temperature raising step includes a step of heating the dispersion obtained by dispersing the resin particles in water from room temperature to the temperature of the maintaining step (hereinafter also referred to as the maintaining temperature).

[0131] The temperature after heating is preferably 50°C or higher, more preferably 80°C or higher, and preferably below the melting point (Tm (°C)) of the resin particles, more preferably below (Tm-20 (°C)). That is, the temperature after heating is preferably 50 to (Tm)°C, more preferably 80 to (Tm-20)°C.

[0132] The dispersion step and the temperature raising step also have the effect of making the resin particles absorb water. From the viewpoint of making the resin particles fully absorb water and plasticize, the total time of the step of obtaining the dispersion and the step of impregnating the foaming agent is preferably 20 minutes or more, and more preferably 30 minutes or more. On the other hand, from the viewpoint of the productivity of the foamed particles, the above time is preferably 60 minutes or less. That is, the above time is preferably 20 to 60 minutes, and more preferably 30 to 60 minutes.

[0133] In addition, from the viewpoint of allowing the resin particles to fully absorb water and become plastic, the heating rate in the heating process is preferably 10°C / minute or less, and more preferably 7°C / minute or less. On the other hand, from the viewpoint of productivity of the foamed particles, the heating rate is preferably 1°C / minute or more, and more preferably 2°C / minute or more. That is, the heating rate is preferably 1 to 10°C / minute, and more preferably 2 to 7°C / minute.

[0134] 《Maintaining Process》

[0135] The holding step is preferably a step of holding the dispersion at a temperature 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher and lower than a temperature 50°C lower than the melting point (Tm) of the resin particles (Tm-50°C) for a holding time of 1 minute to 60 minutes.

[0136] From the viewpoint of allowing the polyamide resin to fully absorb water and become plastic and from the viewpoint of allowing the foaming agent to be uniformly impregnated into the mixed resin, the holding temperature of the dispersion in the holding step is preferably a temperature 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher, more preferably a temperature 80°C lower than Tm (Tm-80°C) or higher, further preferably a temperature 70°C lower than Tm (Tm-70°C) or higher, further preferably a temperature 65°C lower than Tm (Tm-65°C) or higher, and preferably a temperature 50°C lower than Tm (Tm-50°C), more preferably a temperature 53°C lower than Tm (Tm-53°C) or lower, and further preferably a temperature 55°C lower than Tm (Tm-55°C) or lower. That is, the above-mentioned holding temperature is preferably (Tm-90)°C or higher and lower than (Tm-50)°C, more preferably (Tm-80) to (Tm-53)°C, further preferably (Tm-70) to (Tm-55)°C, and further preferably (Tm-65) to (Tm-55)°C.

[0137] Usually, when manufacturing foamed particles using a general-purpose resin such as a polypropylene resin as a base resin, the raw material resin is maintained near the melting point. However, in the method for manufacturing foamed particles of the present invention, it is preferred to manufacture the foamed particles by maintaining the particles at a temperature that is 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher and lower than a temperature that is 50°C lower than Tm (Tm-50°C). The reason is believed to be as follows: Since polyamide resins are hygroscopic, the melting point is greatly reduced by plasticizing the resin particles using water used as a dispersion liquid. As a result, foamed particles having a desired apparent density and independent cell ratio can be manufactured at a temperature that is significantly lower than the melting point of the resin particles.

[0138] From the viewpoint of uniformly impregnating the foaming agent into the mixed resin to obtain foamed particles with a high independent bubble rate, the holding time in the holding process is preferably 1 minute or more, more preferably 5 minutes or more, more preferably 10 minutes or more, and more preferably 13 minutes or more. In addition, from the viewpoint of the productivity of the foamed particles and the viewpoint of preventing the hydrolysis of the polyamide resin, the holding time in the holding process is preferably 60 minutes or less, more preferably 40 minutes or less, more preferably 30 minutes or less, more preferably 20 minutes or less, and more preferably 18 minutes or less. That is, the above holding time is preferably 1 to 60 minutes, more preferably 1 to 40 minutes, more preferably 5 to 30 minutes, more preferably 10 to 20 minutes, and more preferably 13 to 18 minutes. By holding for the above time, polyamide resin foamed particles with low apparent density and high independent bubble rate can be obtained. The holding process can also be set to multiple stages within the temperature range, and it can also spend sufficient time in the temperature range and slowly heat up. From the viewpoint of enabling easy production, it is preferred to set one stage within the temperature range (maintain the temperature constant) and maintain the temperature for the above-mentioned time.

[0139] From the viewpoint of uniformly impregnating the mixed resin with the foaming agent, the holding step is preferably performed under pressure, and preferably the same pressure as the impregnation pressure is maintained. The pressure in the container containing the dispersion is preferably 1.5 MPa (G) or more, and more preferably 2.5 MPa (G) or more. In addition, the pressure in the container containing the dispersion is preferably 7.0 MPa (G) or less, and more preferably 5.0 MPa (G) or less. That is, the pressure in the above-mentioned container is preferably 1.5 to 7 MPa (G), and more preferably 2.5 to 5 MPa (G).

[0140] 《Foaming process》

[0141] The foaming step is a step of foaming the resin particles impregnated with a foaming agent. The foaming method of the resin particles is not particularly limited, but preferably, after the holding step, the resin particles impregnated with a foaming agent are released together with water into an atmosphere having a pressure lower than the pressure in the holding step (usually at atmospheric pressure) to foam them.

[0142] From the viewpoint of obtaining foamed particles with low apparent density and high independent cell ratio, the temperature Te of the dispersion before foaming (hereinafter also referred to as the foaming temperature) is preferably a temperature 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher, more preferably a temperature 80°C lower than Tm (Tm-80°C) or higher, further preferably a temperature 70°C lower than Tm (Tm-70°C) or higher, and further preferably a temperature 65°C lower than Tm (Tm-65°C) or higher. In addition, the foaming temperature is preferably lower than a temperature 50°C lower than the melting point (Tm) of the resin particles (Tm-50°C), more preferably a temperature 53°C lower than Tm (Tm-53°C) or lower, and further preferably a temperature 55°C lower than Tm (Tm-55°C) or lower. That is, the foaming temperature is preferably (Tm-90)°C or higher and lower than (Tm-50)°C, more preferably (Tm-80) to (Tm-53)°C, further preferably (Tm-70) to (Tm-55)°C, and further preferably (Tm-65) to (Tm-55)°C.

[0143] The pressure immediately before release in the foaming process (foaming pressure) is preferably 0.5 MPa (G) or more, more preferably 1.5 MPa (G) or more, and even more preferably 2.5 MPa (G) or more. In addition, the foaming pressure is preferably 10 MPa (G) or less, more preferably 7 MPa (G) or less, and even more preferably 5 MPa (G) or less. That is, the foaming pressure is preferably 0.5 to 10 MPa (G), more preferably 1.5 to 7 MPa (G), and even more preferably 2.5 to 5 MPa (G).

[0144] [Expanded Bead Molded Article]

[0145] The polyamide resin expanded bead molded article of the present invention is an expanded bead molded article in which the expanded beads are fused together. That is, the expanded bead molded article of the present invention is an expanded bead molded article obtained by in-mold molding the expanded beads of the present invention (in-mold expanded bead molded article).

[0146] The foamed beads of the present invention have excellent weldability and recovery properties, and can suppress the shrinkage after molding, so the foamed bead molded body can suppress the shrinkage after molding and has a good appearance. The foamed bead molded body obtained by in-mold molding of the foamed beads of the present invention can suppress the shrinkage after molding, so a thick molded body can be obtained appropriately. The thickness of the foamed bead molded body is preferably 30 mm or more, and more preferably 40 mm or more.

[0147] The in-mold molding method can adopt a conventionally known method, but preferably uses heating using steam. The polyamide resin in the expanded particles absorbs water and becomes plasticized by steam, so the molding pressure can be reduced. In addition, if the obtained molded body is dried to remove moisture, the original physical properties of the polyamide resin are restored, and the molded body becomes a molded body with high heat resistance.

[0148] The expanded beads of the present invention can be made into an expanded bead molded article having excellent in-mold moldability. Specifically, the water cooling time can be shortened, and as a result, the overall molding time can be shortened, which is preferred.

[0149] The water cooling time of the foamed particle molded body is calculated as follows. First, the obtained foamed particles are filled into a molding mold, and in-mold molding is performed by steam heating to obtain a plate-shaped foamed particle molded body. The heating method is to supply steam for 5 seconds while the discharge valves of the molds on both sides are open to perform preheating (exhaust process), then supply steam from the movable side mold, and then supply steam from the fixed side mold, and then heat until the pressure reaches the molding heating steam pressure (molding pressure = molding steam pressure). After the heating is completed, the pressure is released, and after water cooling until the surface pressure caused by the foaming force of the molded body is reduced to 0.04MPa (G), the mold is opened and the molded body is taken out from the mold. The water cooling time of the foamed particle molded body is set to the water cooling time (seconds) required from the start of water cooling to the surface pressure reaching 0.04MPa (G). In the present invention, as a reason for being able to shorten the water cooling time when the foamed particles are in-mold molded, the following reasons can be considered. When the expanded particles are molded, the expanded particles are heated and pressurized by steam, and the expanded particles are secondary expanded, and the expanded particles are mutually fused. At this time, by including a specific ratio of a xylene-containing polyamide resin in the base resin, excessive secondary expansion can be suppressed, and the maximum surface pressure can be suppressed from being excessively increased. As a result, it is considered that the surface pressure decreases faster during water cooling, and the water cooling time can be shortened.

[0150] <Molding density>

[0151] From the viewpoint of obtaining a molded product having excellent lightness, resilience and weldability, the density of the expanded bead molded product (molded product density) is preferably 10 kg / m 3 More than 30 kg / m 3 More preferably, 50 kg / m 3 More preferably, 60 kg / m 3 More than, and preferably 350kg / m 3 Below, more preferably 300kg / m 3 Below, more preferably 250kg / m 3 Below, more preferably 200kg / m3 That is, the density of the molded body is preferably 10 to 350 kg / m 3 , more preferably 30 to 300 kg / m 3 , more preferably 50 to 250 kg / m 3 , more preferably 60 to 200 kg / m 3 .

[0152] The density of the molded body is measured by the following method. The foamed particle molded body is placed under the conditions of a relative humidity of 50%, a temperature of 23°C, and 1 atm for 2 days. Next, a container filled with water at a temperature of 23°C is prepared, and an arbitrary amount of the foamed particle molded body (mass W[g]) is sunk into the water in the container using a tool such as a wire mesh. Then, taking into account the volume of the tool such as the wire mesh, the volume V[L] of the foamed particle molded body read from the part where the water level rises is measured. The mass W[g] of the foamed particle molded body placed in the container is divided by the volume V[L] (W / V), and the unit is converted into [kg / m 3 ] and calculate the density of the formed body.

[0153] Example

[0154] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited thereto.

[0155] The polyamide resins, resin particles, foamed particles, and molded articles in Examples and Comparative Examples were measured and evaluated by the following methods.

[0156] [Measurement and evaluation]

[0157] <Resin particles>

[0158] (Melting Point)

[0159] Based on JIS K7121-1987, the melting point of polyamide resin particles is measured by heat flux differential scanning calorimetry. Under the condition of 30 mL / min of nitrogen inflow, after heating from 30 ° C to a temperature 30 ° C higher than the melting peak at the end (the first heating) at a heating rate of 10 ° C / min for melting, then after the temperature is kept for 10 minutes, it is cooled to 30 ° C at a cooling rate of 10 ° C / min, and heated to a temperature 30 ° C higher than the melting peak at the end of the melting peak at a heating rate of 10 ° C / min again for melting, and the melting point is obtained as the peak apex temperature of the melting peak of the second DSC curve thus obtained. In addition, as a measuring device, a high-sensitivity differential scanning calorimeter "EXSTAR DSC7020" (made by Seiko Nano Technology (SIINanoTech) Co., Ltd.) is used. In addition, in order to avoid high temperature and high humidity conditions and prevent hydrolysis, the resin particles used as test pieces were used for melting point measurement after the nitrogen atmosphere was set in a desiccator and then evacuated to keep the moisture content below 1000 mass ppm and stored for 24 hours. In addition, when the DSC curve has multiple melting peaks, the peak top temperature of the melting peak with the largest area is used as the melting point.

[0160] <Foamed particles>

[0161] (Melting point and heat of fusion)

[0162] Based on the melting peak obtained in the first DSC curve obtained when the foamed beads are used as test pieces and the temperature is increased from 30°C to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min by heat flux differential scanning calorimetry, the temperature of the top of each melting peak and the heat of melting are calculated. In addition, as a measuring device, a high-sensitivity differential scanning calorimeter "EXSTAR DSC7020" (manufactured by Seiko NanoTech Co., Ltd.) was used. Figure 1 (First DSC curve) is described.

[0163] exist Figure 1 In the first DSC curve shown, there are three melting peaks. The peak on the lowest temperature side is the melting peak (I) inherent to polyamide resin A, the second peak is a high temperature peak (melting peak (II)), and the peak on the highest temperature side is the melting peak (III) inherent to polyamide resin B. The temperature of the top of each melting peak is the temperature of the point where the heat absorption of each peak is the largest. Figure 1In the DSC curve shown, the melting heat of the apex of each melting peak is equivalent to the area of ​​each melting peak, which is obtained as follows. First, draw a straight line (derived from the baseline of the melting peak of polyamide resin A) connecting the point of 120°C on the DSC curve and the point of the melting end temperature of the melting peak (II) on the DSC curve. From the point on the DSC curve corresponding to the valley between the melting peak (I) and the melting peak (II) to the baseline of the melting peak derived from the polyamide resin A, the melting peak (I) and the melting peak (II) are divided by a straight line perpendicular to the temperature of the horizontal axis of the chart. The area 1 of the peak on the low temperature side divided is equivalent to the melting heat of the melting peak (I) inherent to the polyamide resin A, and the area 2 of the peak on the high temperature side divided is equivalent to the melting heat of the high temperature peak (melting peak (II)) derived from the polyamide resin A. Next, a straight line (base line of the melting peak inherent to polyamide resin B) is drawn connecting the point on the DSC curve showing the melting start temperature of the melting peak (III) and the point showing the melting end temperature of the melting peak (III) inherent to polyamide resin B. The area 3 of the portion surrounded by the baseline of the melting peak derived from the polyamide resin B and the DSC curve is equivalent to the heat of fusion of the melting peak (III) inherent to polyamide resin B.

[0164] (Apparent density)

[0165] The apparent density of the expanded particles was measured by the following method. A graduated cylinder filled with water at a temperature of 23° C. was prepared, and the volume of about 500 cm 2 of the expanded particles was measured after being left for 2 days under the conditions of a relative humidity of 50%, 23° C., and 1 atm. 3 The mass W1 of the foamed particles is then sunk into the measuring cylinder using a wire mesh. Taking into account the volume of the wire mesh, the volume V1 [cm 3 ], the mass W1[g] of the foamed particles is divided by the volume V1 to calculate (W1 / V1), and the unit is converted to [kg / m 3 ], calculate the apparent density of the foamed particles.

[0166] (Average bubble diameter)

[0167] The average bubble diameter of the expanded particles is measured by the following method. First, the expanded particles are roughly divided into two equal parts in a manner passing through the center of the expanded particles, and a photograph of the cut surface is taken using a scanning electron microscope. Next, in the obtained cross-sectional photograph, straight lines are drawn at equal intervals in 8 directions from near the center of the expanded particle cut surface, and the number of bubbles intersecting the straight lines is counted. The total length of the straight line is divided by the number of bubbles counted, and the obtained value is used as the bubble diameter of the expanded particles. The same operation is performed on 30 expanded particles, and the arithmetic mean of the bubble diameters of the expanded particles is used as the average bubble diameter of the expanded particles.

[0168] (Independent bubble rate)

[0169] The independent cell rate of the foamed particles is measured by the following method. The value Vx of the true volume of the foamed particles (the sum of the volume of the resin constituting the foamed particles and the total volume of the bubbles in the independent bubble part of the foamed particles) is measured according to step C described in ASTM-D2856-70. In the measurement of the true volume Vx, an air comparison type densitometer "930" manufactured by Toshiba Beckman Co., Ltd. is used. Next, the independent cell rate is calculated by the following formula (1), and the arithmetic mean of the 5 measurement results is obtained.

[0170] Closed cell ratio (%) = (Vx-W / ρ) × 100 / (Va-W / ρ)…(1)

[0171] Vx: The true volume of the expanded particles measured by the above method (cm 3 )

[0172] Va: Apparent volume of expanded particles (cm 3 )

[0173] W: Mass of the sample for foamed particle measurement (g)

[0174] ρ: Density of the resin constituting the foamed particles (g / cm 3 )

[0175] <Molded body>

[0176] (Molding body density)

[0177] The density of the molded body is measured by the following method. Using the foamed particles obtained in each embodiment and each comparative example, a foamed particle molded body is prepared by the method described in the later-described <Preparation of a mixed resin foamed particle molded body>. The foamed particle molded body is placed under the conditions of a relative humidity of 50%, a temperature of 23°C, and 1 atm for 2 days. Next, a container filled with water at a temperature of 23°C is prepared, and an arbitrary amount of the foamed particle molded body (mass W[g]) is sunk into the water in the container using a tool such as a wire mesh. Then, taking into account the volume of the tool such as the wire mesh, the volume V[L] of the foamed particle molded body read from the part where the water level rises is measured. The mass W[g] of the foamed particle molded body placed in the container is divided by the volume V[L] (W / V), and the unit is converted into [kg / m 3 ] and calculate the density of the formed body.

[0178] (Shrinkage)

[0179] Using the foamed particles obtained in each embodiment and each comparative example, a foamed particle molded body is prepared by the method described in the "Preparation of a Mixed Resin Foamed Particle Molding Body" described later. Then, after standing for 24 hours under an environment of 23°C and a relative humidity of 50%, the size of the foamed particle molded body is measured, and the lengths of the longitudinal, transverse and thickness are set to a', b', c', respectively, and the lengths of the longitudinal, transverse and thickness as the size (internal dimension) of the mold are set to a, b, c, respectively, and the value represented by the following formula at this time is taken as the molding shrinkage (%) of the molded body. The smaller the value of the molding shrinkage of the molded body, the more the molding shrinkage is suppressed, so it is preferred.

[0180] Molding shrinkage (%) = [(a-a') / a+(b-b') / b+(c-c') / c] × 100 / 3

[0181] (Water cooling time)

[0182] Using the foamed beads obtained in each example and each comparative example, a foamed bead molded body was produced by the method described in <Production of Mixed Resin Foamed Bead Molded Body> described later, and the time required from the start of water cooling until the surface pressure reached 0.04 MPa (G) was defined as the water cooling time (seconds).

[0183] (Forming cycle)

[0184] Using the foamed beads obtained in each embodiment and each comparative example, a foamed bead molded body was prepared by the method described in the <Preparation of a mixed resin foamed bead molded body> described later, and the time taken from the start of closing the open mold to the time when the surface pressure caused by the foaming force of the molded body dropped to 0.04 MPa (G) and the mold was released was measured. The shorter the molding cycle time, the shorter the molding cycle can be, so it is preferred.

[0185] (Welding rate)

[0186] The fusion rate of the foamed particle molded body is measured by the following method. For one side of the surface of the foamed particle molded body obtained in each embodiment and each comparative example, a cut of about 10 mm depth is made in the thickness direction at a position where the longitudinal length of the test piece is divided into two equal parts, and the molded body is bent from the cut portion to break it. The ratio of the number m of foamed particles whose material is destroyed on the fracture surface to the number n of all foamed particles on the fracture surface is calculated (m / n×100[%]). In addition, in the case where the molded body cannot be broken even if it is bent, the fusion rate is 100%. The above measurement is carried out 5 times using different test pieces, and the material destruction rate of each is calculated, and their arithmetic average is taken as the fusion rate.

[0187] (Resilience)

[0188] The resilience of the foamed particle molded body is measured by the following method. The thickness of the end portion (10 mm inside from the end) and the center portion (the portion that divides the longitudinal and transverse directions into two equal parts) of the foamed particle molded body corresponding to the size of the flat-plate-shaped mold used in the in-mold molding is measured. Next, the thickness ratio of the foamed particle molded body is calculated (thickness of the center portion of the molded body / thickness of the end portion of the molded body × 100 (%)) and evaluated as follows. In addition, the thickness measurement is carried out on the foamed particle molded body produced by the method described in the <Production of Mixed Resin Foamed Particle Molding Body> described later.

[0189] A: The thickness ratio is 95% or more.

[0190] B: The thickness ratio is less than 95% and 90% or more.

[0191] C: The thickness ratio is less than 90%.

[0192] (Crystallite size)

[0193] The crystallite size of the foamed particle molded body is measured by the following method. The foamed particle molded body is used as a test piece, and X-ray diffraction (XRD) measurement is performed by the reflection method using an X-ray scattering device "Smart Lab SE" (manufactured by Rigaku Corporation). The detector uses a one-dimensional semiconductor detector D / teX Ultra250. The sample uses a foamed particle molded body sliced ​​in a manner such that the sample thickness becomes about 1.0 mm. In addition, the standard substance lanthanum hexaboride is measured to obtain b. Using software (trade name: Igor Pro Version6.3.2.3, manufactured by Wavemetrics), assuming a Gaussian function as the peak shape, the obtained one-dimensional X-ray diffraction spectrum is peak separated according to the diffraction peaks originating from the crystal and the diffraction peaks originating from the amorphous. In addition, the peak separation is performed by automatic fitting. The half-height full width β (rad) of the peak with the narrowest peak width among the peaks obtained by peak separation is calculated, and the half-height full width β is used to calculate the crystallite size D of the foamed particle molded body according to the following formula (2). In the formula (2), λ is the wavelength of the X-ray, and θ is the Bragg angle at the peak position (half of the diffraction angle 2θ).

[0194] [Number 1]

[0195]

[0196] [Production of mixed resin particles, mixed resin foamed particles, and mixed resin foamed particle molded body]

[0197] Table 1 shows the polyamide resins and the like used for producing the mixed resin particles and the mixed resin foamed particles.

[0198] [Table 1]

[0199]

[0200] Examples 1, 2, 4 to 9, Comparative Examples 2, 4 to 7

[0201] <Production of mixed resin particles>

[0202] The polyamide resins listed in Tables 2 to 4 as polyamide resin A and polyamide resin B were supplied to an extruder in the blending ratios listed in Tables 2 to 4, talc "Talc PK-S" (manufactured by Hayashi Kasei Co., Ltd.) was supplied as a bubble regulator in the amounts listed in Tables 2 to 4, aromatic polycarbodiimide "Stabaxol P" (manufactured by Rhein Chemie Co., Ltd.) was supplied in 1.0 mass % as a terminal blocking agent, copper iodide of 0.05 mass % and potassium iodide of 0.2 mass % were supplied as a heat stabilizer, and carbon black was supplied in the amounts shown in Tables 2 to 4 as a colorant, and melt-kneaded to obtain a melt-kneaded product. The melt-kneaded product was extruded from the fine hole of the joint installed at the front end of the extruder in the form of a strand with a circular cross section, and the extruded strand was water-cooled, cut by a granulator so that the average mass per 1 mass was 2 mg, and dried to obtain granular mixed resin particles. The melting points of the resin particles are shown in Tables 2 to 4.

[0203] <Production of mixed resin foamed particles>

[0204] 500g of the obtained mixed resin particles and 3.5 liters of water as a dispersion medium are placed in a 5-liter autoclave equipped with a stirrer. Furthermore, 0.3 parts by mass of kaolin as a dispersant and 0.004 parts by mass of sodium alkylbenzene sulfonate as a surfactant are added to 100 parts by mass of the mixed resin particles. While stirring the contents in the autoclave, the temperature is raised from room temperature (23°C) to the holding temperature (melting point of the resin particles -55°C), and carbon dioxide as a foaming agent is pressed into the autoclave until the pressure in the autoclave reaches the impregnation pressure (4.0MPa(G)). At this time, the heating time from room temperature (23°C) to the holding temperature (melting point of the resin particles -55°C) is 40 minutes. Next, the temperature is maintained at the holding temperature (melting point of the resin particles -55°C) and 4.0MPa(G) for 15 minutes.

[0205] Then, the mixed resin particles impregnated with the foaming agent are released together with the dispersion medium under atmospheric pressure (0.1 MPa). The foaming temperature (i.e., the temperature of the dispersion before foaming) is (melting point of the resin particles - 55) °C. The obtained mixed resin foamed particles are aged in an oven at 60 °C for 24 hours and then gradually cooled to obtain mixed resin foamed particles. The obtained mixed resin foamed particles are subjected to the above-mentioned measurements. The results are shown in Tables 2 to 4.

[0206] <Water content and internal pressure application>

[0207] Use the above-mentioned mixed resin foam particles, put the mixed resin foam particles and water into a plastic bag, seal the mouth of the plastic bag and shake it thoroughly to mix it thoroughly to make it contain water. Then, put 180g of the water-containing mixed resin foam particles into a 3-liter pressure-resistant container with a pressurization temperature set to 40°C. Put the above-mentioned mixed resin foam particles into a pressure-resistant container and seal it, and at the same time press in air as a physical foaming agent to give internal pressure. The internal pressure is given by setting the pressure (pressurization pressure) in the pressure-resistant container to 0.12MPa(G) and the pressurization time to 16 hours.

[0208] <Production of mixed resin expanded particle molded body>

[0209] The mixed resin foamed particles are used to make a foamed particle molded body. The mold is narrowed from the open state, and the obtained mixed resin foamed particles are filled into a flat plate molding mold with a length of 200 mm × a width of 65 mm × a thickness of 40 mm in a state where the mold is slightly opened and the crack is enlarged by 4 mm (i.e., the crack is 10%). After the filling is completed, the mold is completely closed, the foamed particles are compressed, and the mold is closed. Then, the mold is molded by steam heating to obtain a plate-shaped foamed particle molded body.

[0210] The heating method is to supply steam for 5 seconds with the discharge valves of the molds on both sides open to perform preheating (exhaust process), then supply steam from the movable side mold with the discharge valve on the fixed side open, and then supply steam from the fixed side mold with the discharge valve on the movable side open, close the exhaust valve, and heat until the pressure reaches the molding heating steam pressure of 0.12MPa (G) (molding pressure = molding steam pressure). After the heating is completed, the pressure is released, and after water cooling until the surface pressure caused by the foaming force of the molded body is reduced to 0.04MPa (G), the mold is opened and the molded body is taken out from the mold. Then, it is left to stand in an oven at 80°C and taken out after 24 hours to obtain a mixed resin foamed bead molded body. The obtained mixed resin foamed bead molded body is measured and evaluated as described above. The results are shown in Tables 2 to 4. In addition, the secondary foaming property of the foamed bead molded bodies of Comparative Examples 4 to 6 is not excellent, and the weldability is poor, so the water cooling time and molding cycle are not evaluated.

[0211] Example 3

[0212] The same operation as in Example 1 was performed except that the polyamide resin A1 was changed to the polyamide resin A2 and the holding temperature and the foaming temperature were set to (melting point of the resin particles - 61) °C to obtain polyamide resin particles, polyamide resin foamed particles and polyamide resin foamed particle molded bodies. The obtained polyamide resin foamed particles and polyamide resin foamed particle molded bodies were subjected to the above-mentioned measurements and evaluations. The results are shown in Table 2.

[0213] Comparative Examples 1 and 3

[0214] Except that polyamide resin B was not used and only polyamide resin A listed in Table 3 was supplied, the same operation as in Example 1 was performed to obtain polyamide resin particles, polyamide resin foamed particles, and polyamide resin foamed particle molded bodies. The obtained polyamide resin foamed particles and polyamide resin foamed particle molded bodies were subjected to the above-mentioned measurements and evaluations. The results are shown in Table 3.

[0215] [Table 2]

[0216]

[0217] [Table 3]

[0218]

[0219] [Table 4]

[0220]

[0221] As can be seen from Tables 2 to 4, the expanded beads obtained in Examples can provide an expanded bead molded body having a shortened molding cycle during in-mold molding, suppressed shrinkage after molding, and excellent weldability.

[0222] Industrial Applicability

[0223] The polyamide resin foamed beads of the present invention can shorten the molding cycle during in-mold molding, suppress shrinkage after molding, and provide foamed bead molded products with excellent weldability. Therefore, they are expected to be further used in automobile parts, electrical products, etc.

Claims

1. A polyamide resin foam particle, which is a polyamide resin foam particle using a mixed resin of a polyamide resin A and a polyamide resin B as a base resin, characterized in that: The polyamide resin A is an aliphatic polyamide, The polyamide resin B is a polyamide resin containing xylene groups, The mass ratio of the polyamide resin A to the polyamide resin B, that is, polyamide resin A:polyamide resin B, is 97:3 to 60:

40.

2. The polyamide resin foamed particles according to claim 1, wherein The polyamide resin B has a melt flow rate of 5 g / 10 min or less at 275° C. and a load of 0.325 kg.

3. The polyamide resin foamed particles according to claim 1 or 2, characterized in that: The expanded particles contain carbon black.

4. The polyamide resin foamed particles according to any one of claims 1 to 3, characterized in that: The melting point (TmA) of the polyamide resin A is higher than 180° C. and lower than 250° C.

5. The polyamide resin foamed particles according to any one of claims 1 to 4, characterized in that: The difference (TmB-TmA) between the melting point (TmA) of the polyamide resin A and the melting point (TmB) of the polyamide resin B is 30° C. or more and 100° C. or less.

6. The polyamide resin foamed particles according to any one of claims 1 to 5, characterized in that: The apparent density of the expanded particles is 10 kg / m 3 Above 300kg / m 3 the following.

7. The polyamide resin foamed particles according to any one of claims 1 to 6, characterized in that: The closed cell ratio of the foamed particles is greater than 70%.

8. A polyamide resin foam particle molded body, characterized in that: A polyamide resin foamed bead molded article obtained by in-mold molding the polyamide resin foamed bead according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Polyamide resin foam-molded article and method for producing polyamide resin foam-molded article

    WO2016147582A1